Addition of a fixed combination of brinzolamide 1%/timolol 0.5% to prostaglandin monotherapy in patients with glaucoma or ocular hypertension - Lorenz K (Dove Medical Press, 2011)
Katrin Lorenz1, Klaus Rosbach2, Andreas Matt3, Norbert Pfeiffer11University Medical Center, Johannes Gutenberg-Universität Mainz, Mainz, Germany; 2Private practice, Mainz, Germany; 3Private practice, Köln-Hohenhaus, GermanyBackground: This study was conducted to evaluate the safety and efficacy of adding a fixed combination of brinzolamide 1%/timolol 0.5% to prostaglandin analog (PGA) monotherapy in patients with primary open-angle glaucoma, pigment dispersion glaucoma, or ocular hypertension who require additional intraocular pressure (IOP) reduction.Methods: This was a prospective, multicenter (n = 5), open-label, single-arm, Phase IV clinical trial in which patients currently being treated with a PGA but requiring additional IOP reduction were administered brinzolamide 1%/timolol 0.5% twice daily as adjunctive therapy to their current PGA monotherapy regimen. The primary objective was to examine the IOP-lowering efficacy of brinzolamide-timolol when used as adjunctive therapy.Results: Forty-seven patients enrolled in and completed the study. After 12 weeks of adjunctive brinzolamide-timolol therapy, the mean IOP of the total patient population decreased from 22.1 mmHg at baseline to 16.7 mmHg. The mean IOP reduction of 5.4 mmHg (24.4%) was both clinically and statistically significant (P < 0.001). This significant decrease in mean IOP at week 12 was maintained across all PGA groups (P < 0.05). No significant differences were observed in symptom frequency between baseline and week 12 for any of the six solicited symptoms. A total of 17 adverse events from six patients was reported, of which ten were drug-related. Most (n = 7) of the drug-related adverse events were mild or moderate in intensity. None of the adverse events required any treatment or resulted in treatment interruption or discontinuation. Of the 90 eligible eyes, 85.6% had a decrease in IOP of at least 3 mmHg from baseline and 98% of patients had a decrease in IOP of ≥1 mmHg.Conclusion: This study suggests that a fixed combination of brinzolamide 1%/timolol 0.5% can provide additional IOP reduction effectively and safely when used as adjunctive therapy for patients receiving insufficient IOP reduction from PGA monotherapy.Keywords: adjunctive therapy, brinzolamide, carbonic anhydrase inhibitor, fixed combination, glaucoma, intraocular pressure